2015
DOI: 10.1080/21645515.2015.1062956
|View full text |Cite
|
Sign up to set email alerts
|

Community awareness, use and preference for pandemic influenza vaccines in Pune, India

Abstract: Vaccination is a cornerstone of influenza prevention, but limited vaccine uptake was a problem worldwide during the 2009–2010 pandemic. Community acceptance of a vaccine is a critical determinant of its effectiveness, but studies have been confined to high-income countries. We conducted a cross-sectional, mixed-method study in urban and rural Pune, India in 2012–2013. Semi-structured explanatory model interviews were administered to community residents (n = 436) to study awareness, experience and preference be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 54 publications
1
31
1
1
Order By: Relevance
“…For the general population, however, limited coverage was more a matter of limited access, cost of the inactivated vaccine, low perceived personal risk after July 2010 when the LAIV became available, inadequate information and a perceived lack of a government mandate endorsing influenza vaccine. 42 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the general population, however, limited coverage was more a matter of limited access, cost of the inactivated vaccine, low perceived personal risk after July 2010 when the LAIV became available, inadequate information and a perceived lack of a government mandate endorsing influenza vaccine. 42 …”
Section: Discussionmentioning
confidence: 99%
“…It is notable that coverage problems typically attributed to vaccine hesitancy of communities in Western Europe and North America were less of an issue than hesitancy among health professionals to use and prescribe the available vaccine. 42 Implications of vaccine hesitancy among professionals extend well beyond pandemic disease control to other settings, especially with regard to prescribing practices for high-risk groups, such as pregnant women, for whom seasonal influenza vaccination has become a priority for influenza control. 3…”
Section: Discussionmentioning
confidence: 99%
“…This study has also found that only 15.8% received advice from doctors regarding influenza vaccination. [ 10 ] For this, appropriate knowledge regarding H1N1 vaccination and infection among physicians is important.…”
Section: Discussionmentioning
confidence: 99%
“…Topics include studies of vaccine acceptance based on awareness, priority and use with a focus on both health care providers and community residents. This work is based on vaccine acceptance and anticipated acceptance studies of oral cholera vaccine in Zanzibar, Kenya and DR Congo (Schaetti et al 2013;Sundaram et al 2016), and a study of influenza vaccine acceptance during the 2009 influenza pandemic in Pune, India (Sundaram et al 2015). More recently, a study of influenza vaccination of pregnant women to protect them and their newborn infants has been developed for WHO.…”
Section: Current Activities and Next Stepsmentioning
confidence: 99%